2012
DOI: 10.1039/c2cc17211a
|View full text |Cite
|
Sign up to set email alerts
|

The role of a conserved threonine residue in the leader peptide of lasso peptide precursors

Abstract: The conserved threonine (Thr) residue in the penultimate position of the leader peptide of lasso peptides microcin J25 and capistruin can be effectively replaced by several amino acids close in size and shape to Thr. These findings suggest a model for lasso peptide biosynthesis in which the Thr sidechain is a recognition element for the lasso peptide maturation machinery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 27 publications
3
71
0
1
Order By: Relevance
“…S1B). Our group has recently investigated the role of threonine in the leader peptides of MccJ25 and capistruin, and found that it is the optimal residue for the production of these peptides in vivo (29,30). Other amino acids similar in size and shape to threonine can be substituted and still lead to efficient production of MccJ25 and capistruin in cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1B). Our group has recently investigated the role of threonine in the leader peptides of MccJ25 and capistruin, and found that it is the optimal residue for the production of these peptides in vivo (29,30). Other amino acids similar in size and shape to threonine can be substituted and still lead to efficient production of MccJ25 and capistruin in cells.…”
Section: Resultsmentioning
confidence: 99%
“…3B) consisting of the atxA1, atxB, and atxC genes (NCBI gene IDs 10053804-10053806). There is a 54 base region between the atxA1 and atxB genes that includes an inverted repeat sequence, a feature that has been observed previously in lasso peptide gene clusters (28), including the cluster that codes for capistruin (30). This sequence was removed from the cluster and replaced with a short sequence that includes an optimized E. coli ribosome binding site (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 In particular, the Thr residue in the penultimate position of the leader peptide is proposed to be a recognition element for the maturation enzymes. 314 The final product is believed to be transported from the cytoplasm by an ABC transporter. 284,315 In contrast to microcin J25 and capistruin, which are encoded by four-gene clusters, lariatins A and B, produced by Rhodococcus jostii , result from a five-gene cluster ( larABCDE ).…”
Section: Lasso Peptidesmentioning
confidence: 99%
“…More recently, the era of lasso peptides discovery guided by a genome mining strategy emerged with the characterization of capistruin from Burkholderia thailandensis . Genome mining approaches either protein homology-based Hegemann et al , b, 2014 or precursor-centric (Maksimov et al 2012b) coupled with state-of-the-art detection methods (Kersten et al 2011) proved extremely efficient for lasso peptide discovery, 24 of the 35 currently known lasso peptides being identified by this way. They are mainly from proteobacteria and less frequently from actinobacteria.…”
mentioning
confidence: 99%